Penerapan Jadwal Retensi Arsip Mahkamah Agung Republik Indonesia - Nusa, Andre Dio; Lawanda, Ike Iswary (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2020)
This study discusses about the Application of the Records Retention Schedule for Records Retention at the Supreme Court Institution of the Republic of Indonesia. The purpose of this research discussion is to discuss the description of the application of Records Retention Schedule (RRS) in the process of administering the archives becoming archives which will be preserved in the Supreme Court institutional archive in accordance with the established RRS guidelines. It is a qualitative research using observation and interview in order to gather information about the implementation of RRS with several archival management units in the Supreme Court Archives Depot. RRS is viewed as merely a policy in the mind of staff of Supreme Court Archives Depot. The volume of archives produced exceeds the capacity according to the requirements. This makes the staff of archive more use their knowledge rather then following the rules in applying in RRS to do appraisal in retention process.